Analyzing the real size of the tourism industry on the basis of an assessment of water consumption patterns - González Pérez, Daniel María; Martín Martín, José María; Guaita Martínez, José Manuel; Morales Pachón, Andrés (Journal of Business Research, 2023)
Studies have shown that records from official hotel occupancy statistics underestimate the volume of tourists arriving in a territory since tourists staying in non-regulated establishments are not registered. The data from online platforms allow a more approximate estimate, however, they do not reflect the real volume of tourists arriving at a destination either. Therefore, it is difficult to know the real dimension of the tourism industry in a tourist destination. This generates problems of public planning and market analysis by companies. An innovative methodology is proposed to estimate the real size of the tourism industry through an assessment of water consumption patterns. An isolated system such as the Balearic Archipelago in Spain was selected to evaluate the proposed model. For this purpose, the availability of water in the territory, the different existing water sources and the volumes of water supplied have been analyzed. The water consumption linked to the different agents have been also studied. The findings indicate that overnight stays not recorded in the official statistics add up to 23%. This must be considered to determine the real impact of tourism on society and on the environment.
Keywords: accommodation; online platforms; tourism industry; water consumption; Scopus; JCR